Agro-poultry farm and community co-existence through micro environmental management and design intervention - Arcena, Jocelyn M. (College of Architecture, University of the Philippines Diliman, 2017)
The Philippines has already hit the 100 million population mark in 2014 (popcom, 2014). Consequently, providing resources for this vast multitude of consumers is a gargantuan challenge that the country has to face. Food security becomes a foremost concern as the Philippines continues to register the highest population growth rates in Asia. The competition for land between a desired increase in agricultural production and uncontrolled urban growth is one issue that impacts on food security as the Philippine population continues to soar. This is well illustrated in the case of livestock production, such as poultry farms - that used to be situated in rural areas due to safety, hygiene and sanitation concerns. As nearby communities develop naturally around the poultry farm production to remote places. Time and again, the cycle repeats itself and problems of economic and social dimensions resurface. This scenario poses the challenge of how design can address and bring together poultry farm production and community habitation into healthy co-existence. This research looks into the potential of using design and environmental management interventions to enable poultry farm production and human habitation to thrive symbiotically in a well-planned setting. It will organize a body of knowledge that serves as basis for the conceptual and design development of "agro-poultry" farm in a healthy combination that fosters food production, agro-tourism, and community living. The thesis will illustrate the major arguments, lessons learned, as well as the design innovations that will enable poultry farm production and communities thrive together.